POTENTIALS OF SORGHUM STALK IN THE PRODUCTIONS OF CEILING BOARDS - Ahmed Bafeto Mohammed; Babagana Makinta; Ahmed Hussaini (International Journal of Innovations in Engineering Research and Technology, 2023)
This research work is centered at studying the potentialities of sorghum stalk in the production of ceiling boards. Other materials like saw dust, sugar cane bagasse, rice husk and waste paper were used by other researchers for the production of ceiling boards excepting sorghum stalk. Sorghum is one of the most widely agricultural crops cultivated in Nigeria but its residues (stalk) are mostly unused. In this research work, sorghum stalk is ground to particles and was mixed with adhesives (gum Arabic, kaolin and white cement) and water to form a paste that was cast in molds. The molds are of 2400 x 1200 x 20 mm, 2400 x 1200 x 10 mm, 2400 x 1200 x 5 mm. 1200 x 1200 x 20 mm, 1200 x 1200 x 10 mm, 1200 x 1200 x 5 mm, 600 x 600 x 20 mm, 600 x 600 x 10 mm, 600 x 600 x 5 mm. After allowing the cast paste to adequately dry for 7 days, the boards are tested for density, water absorption capacity and thermal conductivity. The tests are conducted using direct method, ASTM D570 and ASTM E1225 respectively. Two ceilings from the same mold 600 x 600 x 20 mm, using (gum Arabic) and (gum Arabic + kaolin + white cement) with density of 1.04 kg/m3, thermal conductivity of 0.079 W/mK have firm physical condition.